Upaya Kelurahan Karang Pilang Dalam Menangani Masalah Stunting Pada Anak Balita - Tutut Putri Ramadani; Adi Soesiantoro (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Stunting is a problem that is often found in developing countries, one of which is Indonesia. The purpose of this article is to find out what efforts have been made by the government/subdistrict officials and the community to overcome the stunting problem in Karang Pilang Subdistrict, and to find out the benefits felt by the community from the efforts made by subdistrict officials in dealing with the stunting problem. This research uses a qualitative research method, a descriptive approach with data collection techniques through observation, interviews and documentation studies. The providers of information in this article are the Village Head, Head of Community Welfare, KSH Coordinator, and families whose children experience stunting. The results of the research show that district officials have made efforts to prevent and overcome stunting in Karang Pilang Subdistrict with several programs, including: conducting socialization about stunting problems, providing supplementary food (PMT) for toddlers and vitamins, checking Mantoux tests at the Karang Pilang Health Post, routine assistance 2- 3x per month, basic food assistance, milk and biscuits, monitoring 1-2x per month, and Direct Cash Assistance (BLT). The benefits felt by the community from these programs include increasing community knowledge about stunting and parenting patterns in children, monitoring children's growth and development, and improving children's nutritional status.